First description of the male of Tegenaria zamanii Marusik & Omelko, 2014 (Araneae: Agelenidae) from northern Iran - Marusik, Yuri M.; Zamani, Alireza (Zootaxa, 2015)
The spider family Agelenidae is a large-sized, globally-distributed family currently comprising 1174 species in 70 genera (World Spider Catalog 2015). The largest genus of the family, Tegenaria Latreille, 1804, consists of 114 accepted species, primarily distributed in the Palaearctic, but also with some species occurring in the Oriental and Nearctic regions (World Spider Catalog 2015; Kaya et al. 2010). So far, only four species of this genus have been recorded from Iran: T. domestica (Clerck, 1757), T. lenkoranica (Guseinov, Marusik & Koponen, 2005), T. pagana C.L. Koch, 1840 and T. zamanii Marusik & Omelko, 2014 (Zamani et al. 2015). Two of these species, T. lenkoranica and T. zamanii are currently known only from females. Latter species was originally described on the basis of recently collected specimens from a cave in Golestan Province of northern Iran, known as Shirabad (= Div Sepid) (Marusik et al. 2014). In July 2015, as a result of a collecting expedition made by the junior author and his team several specimens were observed and photographed in their natural habitat. A single adult male was collected, which is described and illustrated here for the first time. The specimen was photographed using an Olympus Camedia E-520 camera attached to an Olympus SZX16 stereomicroscope. Digital images were prepared using “CombineZP” image stacking software. Lengths of the leg measurements were measured on the dorsal side. The description of the palp refers to the left one. All measurements are given in millimetres. Measurements of palp and leg are listed as: total length (femur, patella, tibia, metatarsus, tarsus). The specimen will be deposited in the Senckenberg Museum, Frankfurt am Main (SMF). The junior author wishes to thank his team for their assistance during the zoological expedition made to the cave and surrounding forests in northern Iran. James W. Berry kindly checked the English of an earlier draft of the manuscript.